A novel methyltransferase from the intracellular pathogen Plasmodiophora brassicae methylates salicylic acid. (25th September 2014) - Ludwig‐Müller, Jutta; Jülke, Sabine; Geiß, Kathleen; Richter, Franziska; Mithöfer, Axel; Šola, Ivana; Rusak, Gordana; Keenan, Sandi; Bulman, Simon
Summary: The obligate biotrophic pathogen Plasmodiophora brassicae causes clubroot disease in Arabidopsis thaliana, which is characterized by large root galls. Salicylic acid (SA) production is a defence response in plants, and its methyl ester is involved in systemic signalling. Plasmodiophora brassicae seems to suppress plant defence reactions, but information on how this is achieved is scarce. Here, we profile the changes in SA metabolism during Arabidopsis clubroot disease. The accumulation of SA and the emission of methylated SA (methyl salicylate, MeSA) were observed in P. brassicae ‐infected Arabidopsis 28 days after inoculation. There is evidence that MeSA is transported from infected roots to the upper plant. Analysis of the mutant Atbsmt1, deficient in the methylation of SA, indicated that the Arabidopsis SA methyltransferase was not responsible for alterations in clubroot symptoms. We found that P. brassicae possesses a methyltransferase (PbBSMT) with homology to plant methyltransferases. The PbBSMT gene is maximally transcribed when SA production is highest. By heterologous expression and enzymatic analyses, we showed that PbBSMT can methylate SA, benzoic and anthranilic acids.